2020
DOI: 10.1073/pnas.1919507117
|View full text |Cite
|
Sign up to set email alerts
|

MYC protein stability is negatively regulated by BRD4

Abstract: The protooncogene MYC regulates a variety of cellular processes, including proliferation and metabolism. Maintaining MYC at homeostatic levels is critical to normal cell function; overexpression drives many cancers. MYC stability is regulated through phosphorylation: phosphorylation at Thr58 signals degradation while Ser62 phosphorylation leads to its stabilization and functional activation. The bromodomain protein 4 (BRD4) is a transcriptional and epigenetic regulator with intrinsic kinase and histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 49 publications
3
101
0
Order By: Relevance
“…Reuss and colleagues (34) showed that MPNST cell lines with complete NF1 deficiency were sensitive to TRAIL-induced cell death that was critically dependent on c-myc . Thus, targeting dysregulated c-myc expression using BRD4 inhibitors may represent a therapeutic opportunity in NF1-associated MPNST (35). There are several other cancer-related genes on Chr8q including UBR5 and RAD21 , and we continue to investigate their potential role in MPNST tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Reuss and colleagues (34) showed that MPNST cell lines with complete NF1 deficiency were sensitive to TRAIL-induced cell death that was critically dependent on c-myc . Thus, targeting dysregulated c-myc expression using BRD4 inhibitors may represent a therapeutic opportunity in NF1-associated MPNST (35). There are several other cancer-related genes on Chr8q including UBR5 and RAD21 , and we continue to investigate their potential role in MPNST tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunction of BET proteins has been strongly linked to the development and progression of various tumors (3). Specifically, BRD4 acts as a synthetic lethal factor of the proto-oncogene MYC, in which BRD4 not only promotes MYC transcription but also regulates its function and degradation (4,5). Given the essential role of BET family proteins in cancer development and inflammation, more than 100 clinical trials are now being carried out to evaluate the benefits of BET inhibitors (BETi) as anticancer therapy (6).…”
Section: Introductionmentioning
confidence: 99%
“…First, BET proteins are known to regulate MYC transcription [ 51 ]. A recent study demonstrated in normal cells that BRD4 has even more control over Myc by binding and phosphorylating Threonine 58 on Myc, leading to degradation [ 52 ]. However, Myc is also capable of regulating BRD4′s histone acetyl transferase activity [ 52 ].…”
Section: Disrupting Myc Stability To Inhibit Its Actions As a Tranmentioning
confidence: 99%
“…A recent study demonstrated in normal cells that BRD4 has even more control over Myc by binding and phosphorylating Threonine 58 on Myc, leading to degradation [ 52 ]. However, Myc is also capable of regulating BRD4′s histone acetyl transferase activity [ 52 ]. Additional studies are needed to better understand how this circular balance may be affected in cancer.…”
Section: Disrupting Myc Stability To Inhibit Its Actions As a Tranmentioning
confidence: 99%
See 1 more Smart Citation